CH

Rút gọn:

A= (2x+3) (4x^2-6x+9)-2(4x^3-1)

B= (x-1)^3-(x+1)^3+6(x+1)(x-1)

HQ
24 tháng 7 2016 lúc 13:41

\(\left(+\right)A=\left(2x+3\right)\left(4x^2-6x+9\right)-2\left(4x^3-1\right).\)

\(A=8x^3-6x^2-18x+27-8x^3+2\)

\(A=6x^2-18x+29\)

\(\left(+\right)B=\left(x-1\right)^3-\left(x+1\right)^3+6\left(x-1\right)\left(x+1\right)\)

\(B=x^3-3x^2+3x+1-x^3-3x^2-3x-1+6\left(x^2-1\right)\)

\(B=-6x^2+6x^2-6\)

\(B=-6\)

Bình luận (0)

Các câu hỏi tương tự
PL
Xem chi tiết
ST
Xem chi tiết
NL
Xem chi tiết
TP
Xem chi tiết
LT
Xem chi tiết
KH
Xem chi tiết
LM
Xem chi tiết
HK
Xem chi tiết
TT
Xem chi tiết